Media engagement - Dahlgren, Peter 1946-; Hill, Annette 1970- (Routledge, Taylor & Francis Group, 2023)
"Written with media students in mind, this accessible book provides both students and researchers with a new perspective on how to research engagement, not as a metric but as a marker of power relations. This book navigates the reader through a tighter analytical notion of engagement within an understanding of media, culture and democracy. Dahlgren and Hill offer a new definition of engagement as an energising internal force, and as such a powerful means to further human agency. From this definition, the book builds a generative theory of engagement as a nexus of relations we make and break with media on a daily basis, with examples from political activism, news and disinformation, and the global pandemic. Dahlgren and Hill identify five parameters of engagement in order to understand the relations we have with media across changing public and mediated spheres. This new perspective offers students and researchers pathways for investigating the meaning of media engagement as a resource for living. It will be particularly useful for undergraduate courses on media audiences and publics, political communication and democracy, media and cultural theory, journalism, and for media, communication and sociology studies more broadly."
Keywords: Politisches Engagement; Massenmedien